2012
DOI: 10.1177/0954405411424696
|View full text |Cite
|
Sign up to set email alerts
|

A thermal-based approach for determining electroplastic characteristics

Abstract: Recent development of electrically assisted manufacturing processes proved the advantages of using the electric current, mainly related with the decrease in the mechanical forming load, and improvement in the formability when electrically assisted forming of metals. The reduction of forming load was formulated previously assuming that a part of the electrical energy input is dissipated into heat, thus producing thermal softening of the material, while the remaining component directly aids the plastic deformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 19 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…[13,25,29] The thermal effect in the experimental data on electroplasticity has to be decoupled to derive the mechanical response due to electrical current under isothermal condition. In the present work, the decoupling of electrical and thermal effect is achieved using finite element simulation, which is more accurate than conventional numerical methods used in earlier works.…”
Section: Discussion On the Resultsmentioning
confidence: 99%
“…[13,25,29] The thermal effect in the experimental data on electroplasticity has to be decoupled to derive the mechanical response due to electrical current under isothermal condition. In the present work, the decoupling of electrical and thermal effect is achieved using finite element simulation, which is more accurate than conventional numerical methods used in earlier works.…”
Section: Discussion On the Resultsmentioning
confidence: 99%
“…A thermal model, accounting for material properties specifically for titanium alloys various levels of plastic deformation, was verified using experimental EAF tests [4]. The conclusions from this section are as follows:…”
Section: Thermal-based Eec Conclusionmentioning
confidence: 97%
“…Figures 4.8 and 4.9 show the true stress-strain profiles of a conventional compression test (at room temperature) and an EAF test for Ti-G2 and Ti-G5, respectively. A die speed of 12.7 mm/min was used and a constant current of 300 A was applied during the EAF test [4]. Both figures show that the flow stress was reduced significantly due to EAF.…”
Section: Force Reduction Due To Eafmentioning
confidence: 99%
See 1 more Smart Citation
“…Ross et al 39 suggested isolatable effects due to electricity such as Joule heating, kinetic energy (pushing dislocations), and retained stress-strain energy, while reporting that a higher resistivity of material induced a greater electroplastic effect. Salandro et al 40,41 assumed that the electric current during deformation produced only heating and deformation energy. He suggested a quantified electroplastic effect coefficient to separate the effects of the electric current into thermal and athermal effects.…”
mentioning
confidence: 99%